Does Formicidae reflect the impact of riparian forest degradation in the Eastern Amazon? - Pinzon Triana, Stefania (2019)
The increasing anthropogenic pressure on Eastern Amazon makes imperative the diagnosis of forest degradation, particularly the effect on key communities within the riparian ecosystems, one of the last remaining Amazonian forests in Maranhão State. The ant family Formicidae is an abundant group in these types of forests plays a fundamental role on the soil and also reflects the land use changes. Therefore, this study aimed to determine the impact of riparian forest successional stages on the Formicidae richness, frequency, and composition. Sampling was performed during both dry and wet seasons using the TSBF method. Collected organisms were identified as morphospecies. Also, species-accumulation curves were created. Linear mixed models were used to evaluate the effects of seasonal, local, and successional stage on ant richness and frequency. Polynomial regression models were applied to investigate the relationship between ant richness and frequency with canopy cover and vegetation height. Lastly, the species composition was represented by the Jaccard similarity index. In total, we observed 1 940 individuals grouped into 86 morphospecies. We obtained more than 80 % of the probable species richness. Ant frequency and richness increased significantly, following the successional stage, with low values in the open areas, especially during the dry season. Canopy cover and vegetation height seemed to affect partially both Formicidae richness and frequency during the dry season. Intermediate and advanced successional areas presented similar composition (50) shared species, followed by the areas of early succession (43) and anthropic use (34). We concluded that the elimination of riparian forests produces a considerable effect on the richness and frequency of the Formicidae family, minimally affecting them in open areas during the dry season, but resulting in losses of 41 % in richness and 56 % in frequency in forest areas when they are transformed into agricultural systems. Nevertheless, succession restores forest structure and functions, thus favoring re-colonization of ant species. Formicidae reflects forest degradation and is a key group in monitoring programs for the conservation/restoration of local riparian forests.